2014
DOI: 10.1111/ajt.12708
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Dendritic Cells Prolong Allograft Survival Through Tmem176b-Dependent Antigen Cross-Presentation

Abstract: z Both authors contributed equally.x Senior authors.The administration of autologous (recipient-derived) tolerogenic dendritic cells (ATDCs) is under clinical evaluation. However, the molecular mechanisms by which these cells prolong graft survival in a donorspecific manner is unknown. Here, we tested mouse ATDCs for their therapeutic potential in a skin transplantation model. ATDC injection in combination with anti-CD3 treatment induced the accumulation of CD8 þ CD11c þ T cells and significantly prolonged all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 52 publications
(74 reference statements)
3
94
1
Order By: Relevance
“…In this study, we implemented these results in a fully mismatched pancreatic islet transplantation model, demonstrating a similar synergistic effect that led to permanent graft acceptance. Importantly, as discussed below, the immune mediators responsible for this sustained islet allograft survival were distinct from those reported previously (23).…”
Section: Foxp3mentioning
confidence: 67%
See 3 more Smart Citations
“…In this study, we implemented these results in a fully mismatched pancreatic islet transplantation model, demonstrating a similar synergistic effect that led to permanent graft acceptance. Importantly, as discussed below, the immune mediators responsible for this sustained islet allograft survival were distinct from those reported previously (23).…”
Section: Foxp3mentioning
confidence: 67%
“…We also showed that by combining these ATDCs with suboptimal treatment with LF 15-0195, a potent and less toxic derivative of the immunosuppressive drug 15-deoxyspergualine, whose main mode of action was reported to be the inhibition of DC maturation in vivo, we were able to promote transplant tolerance (19)(20)(21)(22). Recently, we showed in a minor mismatched skin allograft model in mice that the combined administration of ATDCs and a short course of a CD3-specific mAb prolonged allograft survival (23).…”
Section: Foxp3mentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, we observed a significant increased expression of IL-6 and IL-10, two cytokines that have been linked with Bregs and RegMCs (24,25), in CD8a-depleted recipients compared with controls. We also observed a significant increase in PirB, Tmem176b, and heme oxygenase-1 (HO-1) expression, and several tolerogenic molecules that are important for the maintenance of tolerance in the graft (23,(26)(27)(28). We also observed a significant upregulation of To explore the potential increase in antiallogeneic effector mechanisms in the CD8a-depleted CD40Ig-treated recipients, possibly through Bregs and RegMCs, as such killer activity has been described for both in the literature (30, 31),we analyzed the cytotoxic activity of splenocytes 120 d after transplantation toward 51 Cr-labeled syngeneic, allogeneic, or third-party Con A blasts.…”
Section: Resultsmentioning
confidence: 79%